Studi Analisis Kematangan Emosi dan Hubungan dengan Penyesuaian Perkawinan di KUA Kecamatan Wonoayu - Nisa, Nurfitriatun; Mukarrom, Azmil (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Early adulthood is a problematic period because during early adulthood there are many problems caused by adjustments to matters related to preparation for marriage. Women more often adapt to their partner's habits, especially at the beginning of marriage. Women who are married to their partners usually experience difficulties in adjusting to their partner's behavior in the early years of their marriage. This research aims to determine the relationship between emotional maturity and marital adjustment in early adulthood in Wonoayu District. This research uses a qualitative approach. The subjects of this research were the Wonoayu District KUA and the Sidoarjo Religious Court. The data collection method used was observation and interviews with the Head of KUA and PA Judges regarding marital adjustment and emotional maturity. The research results show that there is a positive and significant relationship between emotional maturity and marital adjustment. The bride and groom course (suscatin) is programmed by the Ministry of Religion for married couples to create a strong and resilient family, so everything needs to be matured, especially emotionally, psychologically, and so on so that they are ready. Because marriage requires serious effort. So it can be concluded that the better the emotional maturity and relationship maturity that the bride and groom prepare and have, the better the relationship will be in the future. Because both partners can easily adjust to the stages of marital adjustment.